2007
DOI: 10.1007/s00422-007-0202-0
|View full text |Cite
|
Sign up to set email alerts
|

Attractor models of working memory and their modulation by reward

Abstract: This work reports an empirical examination of two key issues in theoretical neuroscience: distractibility in the context of working memory (WM) and its reward dependence. While these issues have been examined fruitfully in isolation (e.g. Macoveanu et al. in Biol Cybern 96(4): 407-19, 2007), we address them here in tandem, with a focus on how distractibility and reward interact. In particular, we parameterise an observation model that embodies the nonlinear form of such interactions, as described in a recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…We show that while a visually guided saccade or memory period will, on their own, bias a subsequent memory-guided saccade, neither are necessary. Furthermore, behavioral studies with distractors show that merely presenting an irrelevant visual stimulus is sufficient to produce an attractive bias (Macoveanu et al 2007;Chumbley et al 2008). These findings suggest that visual target presentation, which occurs in both saccade-only and memoryonly trials, is the most likely cause for the observed response bias in every case.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We show that while a visually guided saccade or memory period will, on their own, bias a subsequent memory-guided saccade, neither are necessary. Furthermore, behavioral studies with distractors show that merely presenting an irrelevant visual stimulus is sufficient to produce an attractive bias (Macoveanu et al 2007;Chumbley et al 2008). These findings suggest that visual target presentation, which occurs in both saccade-only and memoryonly trials, is the most likely cause for the observed response bias in every case.…”
Section: Discussionmentioning
confidence: 74%
“…When the two peaks are far apart, intermediate nodes are not excited and the global inhibition quashes the weaker bump (usually the distractor bump) before it has a chance to distort the bump representing the correct memory location. The predicted spatial pattern of within-trial interference has been replicated in behavioral studies (Macoveanu et al 2007;Chumbley et al 2008).…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…8 Model of the biological associative memory 1. Stochastic neuron models enable the study and understanding of probabilistic decision making [44]. 2.…”
Section: Applications Of the Stochastic Neuron Modelmentioning
confidence: 99%